Karya Bidang Program Radio “Jateng Pagi” di RRI PRO 1 Semarang (Pengarah Acara) - Nungki Dwi Widyastuti; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Radio Republik Indonesia is the oldest radio in Indonesia and the only government-owned radio that has the vision to realize Indonesia's public broadcasting institution as the largest networked radio, nation character builder, world-class. RRI has very wide network from Aceh to Papua. However, there are still many young people who do not know Radio Republik Indonesia. The number of private radios emerging has made RRI's popularity waning. The main reason is the image of RRI as a radio news and radio for parents, so less attractive for young people who are thirsty for entertainment and the latest things. One solution is to re-concept or re-create